Anakinra Drug Retention Rate and Predictive Factors of Long-Term Response in Systemic Juvenile Idiopathic Arthritis and Adult Onset Still Disease - Sota, Jurgen; Rigante, Donato; Ruscitti, Piero; Insalaco, Antonella; Sfriso, Paolo; de Vita, Salvatore; Cimaz, Rolando; Lopalco, Giuseppe; Emmi, Giacomo; La Torre, Francesco; Fabiani, Claudia; Olivieri, Alma Nunzia; et al. (Frontiers in Pharmacology, 2019)
Background and objective: Only a few studies have reported long-term efficacy of interleukin (IL)-1 inhibition in systemic juvenile idiopathic arthritis (sJIA) and adult onset Still disease (AOSD). Herein we report on the effectiveness of Anakinra (ANA), expressed in terms of drug retention rate (DRR), and evaluate the predictive factors of drug survival in patients with both sJIA and AOSD. Patients and methods: This is a multicentre study reviewing retrospectively the medical records from 61 sJIA and 76 AOSD patients treated with ANA in 25 Italian tertiary referral centers. Results: The cumulative retention rate of ANA at 12-, 24-, 48- and 60-months of follow-up was 74.3%, 62.9%, 49.4% and 49.4%, respectively, though without any significant differences between sJIA and AOSD patients (p=0.164), and between patients treated in monotherapy compared to the subgroup co-administered with conventional disease modifying anti-rheumatic drugs (cDMARDs) (p=0.473). On the other hand, a significant difference in DRR was found between biologic-naïve patients and those previously treated with biotechnologic drugs (p=0.009), which persisted even after adjustment for pathology (p=0.013). In the regression analysis, patients experiencing adverse events (AEs) (HR=3.029 [C.I. 1.750-5.242], p<0.0001) and those previously treated with other biologic agents (HR=1.818 [C.I. 1.007-3.282], p=0.047) were associated with a higher hazard ratio of ANA discontinuation. The median treatment delay was significantly higher among patients discontinuing ANA (p<0.0001). Significant corticosteroid-sparing (p=0.033) and cDMARD-sparing effects (p<0.0001) were also recorded. Less than 1/3 of our cohort developed AEs, and 85% were deemed mild in nature, with 70% of them involving the skin. Conclusions: Our findings display an overall excellent DRR of ANA on the long run for both sJIA and AOSD, that may be further optimized by closely monitoring patient’s safety issues and employing this IL-1 inhibitor as a first-line biologic as early as possible. Moreover, ANA allowed a significant other drug-sparing effect and showed an overall good safety profile.